CANONICAL RELATIONS OF BASIC-MOTOR AND SITUATIONAL- MOTOR ABILITIES IN SOCCER PLAY - Alen Kapidžić; Miroslav Smajić; Azer Korjenić (Sport Scientific And Practical Aspects, 2025)
Research has been applied on 155 students – 1st and 2nd year of Faculty of sportand physical education in Tuzla, age 19-22. We used a system of 15 variables of basic-motor abilities which represents predictor system and 9 situation motor abilities in soccer which represents criterion system. Primary goal of this research is to establish relation between some of motor and situation-motor abilities in soccer, that while be established by treatment of this special point by canonical correlation analysis. Pursuant to obtained data we expect better results in situational-motor abilities at participants with better coordination abilities and higher level of explosive force and repetitive force.